NPA Management in Regional Rural Banks (A Case Study of Manipur Rural Bank) - Singh, N. Tejmani; Singh, Jitendra (Journal of Commerce and Trade, 2009)
The present study is an attempt to analyze the Non Performing Assets (NPAs) of Manipur Rural Bank (MRB). Adequate credit availability to the rural masses is also one of the main objectives of the Government of India. It will bring the socio-economic development of the country. To obtain this objective, Regional Rural Bank (RRBs) were established (first five RRBs established in 1975) to provide loans and advances to the common people who lived in rural areas. Manipur Rural Bank (MRB) has also been taking its role for the economic development of the rural people since its inception in Manipur (1981). Unfortunately, this bank is now facing the problem of NPAs. Non recovery also affects the profitability of banks. In fact, it is the level of Non-Performing assets which to a great extent, differentiate between a good and a bad bank.